O psicólogo na rede pública de educação: concepções, formação e atuação profissional - Cavalcante, Lorena de Almeida (2015)
This study aimed to deepen the comprehension about school’s psychologist’s professional qualification, conceptions and practices. School psychologist composes effectively professional staff of João Pessoa since 98, through law n° 8682/98, joining on schools by public tender or by hires. To obtain information about school psychologist’s professional identity and the conceptions that guide their practices, there were interviewed 55 professionals. The interview were registered by a voice recorder and literally transcript to analysis. The results indicated that the majority of professionals do not present qualification in School Psychology area, relating job’s opportunity as one of the motivations to work in this area, what have consequences to the practices in curse. The majority of professionals concluded Psychology’s university more than 20 years ago and are not involved in a continue qualification in service that makes possible to review identity and practices of school psychologist and the mobilization of the competences that are necessary on the school context. Besides that, were investigated the practices developed by school psychologists and those that the consider favorable to school context. Were verified divergences between these practices, what may be related to the difficulties related by school psychologists. It is suggested the importance of realize constantly studies in the area, aiming to know practices that promote development and learning processes in educational contexts.